Life at risk - Nawaz, Muhammad Amjad (SLU/Dept. of Urban and Rural Development, 2012)

(untitled)
The issue of child labor and hazardous work is a reality in many developing countries including Pakistan. With its high population density, mostly in the rural areas, a majority of the households engage in activities that are geared towards survival without considering the negative implications. Children who are usually of school going age and on whose shoulders the future depend are forced to work, often in hazardous conditions.